Minimally invasive treatments for early colorectal cancer: comparison of endoscopic resection and laparoscopic surgery - Kyeong Eui Kim; Yoo Jin Lee; Ju Yup Lee; Woon Kyung Jeong; Seong Kyu Baek; Sung Uk Bae (Korean Journal of Clinical Oncology, 2022)
Purpose Endoscopic treatment and laparoscopic surgery are minimally invasive options for early treatment of colorectal cancer, however, more evidence of the long-term outcomes between the two procedures is needed to guide clinical decisions. Therefore, this study aimed to compare the oncologic outcomes between endoscopic and laparoscopic treatment for early colorectal cancer. Methods The study group included 60 patients who underwent endoscopic treatment and 38 patients who underwent laparoscopic surgery for early colorectal adenocarcinoma between January 2010 and December 2013 at a single study site. Results Histopathological diagnoses showed that 43 (78.3%) carcinomas in the endoscopic submucosal dissection group were mucosal to sm1, 13 (21.7%) were sm2 or deeper, and 17 high-risk cases (28.3%) in the endoscopic group underwent additional surgery. The median operation time, time to sips of water, and length of hospital stay were significantly shorter in the endoscopic group than in the laparoscopic group. The overall survival rates of patients in the endoscopic group and laparoscopic groups were 91.5% and 87.4%, respectively (P=0.391), and the disease-free survival rates were 90.4% and 87.4% (P=0.614), respectively. Systemic recurrences occurred in two patients (1.6%) in the endoscopic group and one patient (2.0%) in the laparoscopic group. Local recurrence combined with systemic recurrence in one patient (0.8%) in the endoscopic group. Conclusion Endoscopic resection for early colorectal cancer can be performed safely with better short-term outcomes and comparable long-term oncological outcomes compared to laparoscopic surgery.